Transcriptomic Analysis of a Diabetic Skin-Humanized Mouse Model Dissects Molecular Pathways Underlying the Delayed Wound Healing Response. - León, Carlos; Garcia-Garcia, Francisco; Llames, Sara; García-Pérez, Eva; Carretero, Marta; Arriba, María Del Carmen; Dopazo, Joaquin; Del Rio, Marcela; Escamez, Maria José; Martínez-Santamaría, Lucía (Genes (Basel), 2020)
Defective healing leading to cutaneous ulcer formation is one of the most feared complications of diabetes due to its consequences on patients' quality of life and on the healthcare system. A more in-depth analysis of the underlying molecular pathophysiology is required to develop effective healing-promoting therapies for those patients. Major architectural and functional differences with human epidermis limit extrapolation of results coming from rodents and other small mammal-healing models. Therefore, the search for reliable humanized models has become mandatory. Previously, we developed a diabetes-induced delayed humanized wound healing model that faithfully recapitulated the major histological features of such skin repair-deficient condition. Herein, we present the results of a transcriptomic and functional enrichment analysis followed by a mechanistic analysis performed in such humanized wound healing model. The deregulation of genes implicated in functions such as angiogenesis, apoptosis, and inflammatory signaling processes were evidenced, confirming published data in diabetic patients that in fact might also underlie some of the histological features previously reported in the delayed skin-humanized healing model. Altogether, these molecular findings support the utility of such preclinical model as a valuable tool to gain insight into the molecular basis of the delayed diabetic healing with potential impact in the translational medicine field.
Keywords: Animals; Diabetes Mellitus, Experimental; Gene Expression Profiling; Gene Expression Regulation; Gene ontology; Humans; Metabolic Networks and Pathways; Mice; Mice, Nude; Microarray Analysis; Molecular Sequence Annotation; Principal Component Analysis; Signal Transduction; Skin; Skin Transplantation; Skin Ulcer; Streptozocin; Tissue Engineering; Transcriptome; Transplantation, Heterologous; Wound Healing

Role of CPI-17 in restoring skin homoeostasis in cutaneous field of cancerization: effects of topical application of a film-forming medical device containing photolyase and UV filters. - Puig-Butille, Joan Anton; Malvehy, Josep; Potrony, Miriam; Trullas, Carles; Garcia-Garcia, Francisco; Dopazo, Joaquin; Puig, Susana (Exp Dermatol, 2013)
Cutaneous field of cancerization (CFC) is caused in part by the carcinogenic effect of the cyclobutane pyrimidine dimers CPD and 6-4 photoproducts (6-4PPs). Photoreactivation is carried out by photolyases which specifically recognize and repair both photoproducts. The study evaluates the molecular effects of topical application of a film-forming medical device containing photolyase and UV filters on the precancerous field in AK from seven patients. Skin improvement after treatment was confirmed in all patients by histopathological and molecular assessment. A gene set analysis showed that skin recovery was associated with biological processes involved in tissue homoeostasis and cell maintenance. The CFC response was associated with over-expression of the CPI-17 gene, and a dependence on the initial expression level was observed (P = 0.001). Low CPI-17 levels were directly associated with pro-inflammatory genes such as TNF (P = 0.012) and IL-1B (P = 0.07). Our results suggest a role for CPI-17 in restoring skin homoeostasis in CFC lesions.
Keywords: Administration, Topical; Adult; Aged; Aged, 80 and over; Biopsy; Deoxyribodipyrimidine Photo-Lyase; Female; Gene Expression Profiling; Gene Expression Regulation, Enzymologic; Gene Expression Regulation, Neoplastic; Homeostasis; Humans; Inflammation; Intracellular Signaling Peptides and Proteins; Liposomes; Male; Middle Aged; Muscle Proteins; Phenotype; Phosphoprotein Phosphatases; Reactive Oxygen Species; Skin; Skin Neoplasms; Ultraviolet Rays